'Effect of Biofertilizer and Humic Acid on Growth and Flowering of Solidago spp. Issue 1 (May 2021) - Salih, Z. K.; Ali, H. M.
Abstract: A pot experiment was carried out in lath house of Horticulture and Landscape Dep / College of Agriculture - Tikrit University for the period from February to December 2020. The experiment included two factors, Humic Acid add (control) and the addition at a concentration of 3 g. L −1, Biofertilizers without addition, Glomus mosseae at rate 50 gm.pot −1 and Bacillus sabtilus . results showed the superiority of the treatment of Mycorrhizae in most of the studied traits, and it gave a plant height 111.52 cm and the number of spores 258.74 .10g m-1 . The addition of was superior and gave 5.84 inflorence stems and 13.95 day vase life. interaction treatment between Mycorrhiza and Humic interaction treatment gave the highest concentration of nitrogen, phosphorus and potassium where 2.08%, 0.323% and 1.70%, respectively.